Effect of SafMannan on Local Iraqi Laying Hens Performance - Yasser J. Jameel1 , Mohannad M. Alrekabi2; Nihad A. Ali3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Phase one laying hens diet were included of two levels of yeast cell wall (YCW) called SafMannan fromPhlio-USA company. A total of 81 Iraqi laying hens 14 weeks’ old were distributed into three treatments.Each treatment has 27 hens were distributed into 27 individual cages (one hen per cage). First group henswere fed on basal diet without supplement (CON). Chicks in second and third group were fed on 250 ppm(Saf 250) and 500 ppm (Saf 500) SafMannan respectively. Body weight were weighted weekly from 14-34weeks; while, egg weight was numbered weekly from 20-34 weeks. Results revealed that body weight wereenhanced significantly (p?0.05) in (Saf 250) and (Saf 500) respectively as compared with the control group(CON). The highest egg weight was found in the group was received (Saf 250). Egg weight were increasesignificantly (p?0.05) in groups were received SafMannan (Saf 250) and (Saf 500) respectively as comparedwith the (CON). In conclusion, adding of SafMannan as a prebiotic in the poultry hens diet at 250 ppm wereenhanced the egg weight and body weight of local Iraqi laying hens.